Vitamin D and Cancer - Vuolo, Laura; di somma, carolina; Faggiano, Antongiulio; Colao, Annamaria A. (Frontiers in Endocrinology, 2012)
Vitamin D system is a complex pathway that includes precursors, active metabolites, enzymes, and receptors. This complex system actives several molecular pathways and mediates a multitude of functions. In addition to the classical role in calcium and bone homeostasis, vitamin D plays “non-calcemic” effects in host defense, inflammation, immunity, and cancer processes as recognized in vitro and in vivo studies. The aim of this review is to highlight the relationship between vitamin D and cancer, summarizing several mechanisms proposed to explain the potential protective effect of vitamin D against the development and progression of cancer. Vitamin D acts like a transcription factor that influences central mechanisms of tumorigenesis: growth, cell differentiation, and apoptosis. In addition to cellular and molecular studies, epidemiological surveys have shown that sunlight exposure and consequent increased circulating levels of vitamin D are associated with reduced reduced occurrence and a reduced mortality in different histological types of cancer. Another recent field of interest concerns polymorphisms of vitamin D receptor (VDR); in this context, preliminary data suggest that VDR polymorphisms more frequently associated with tumorigenesis are Fok1, Bsm1, Taq1, Apa1, EcoRV, Cdx2; although further studies are needed to clarify their role in the cancer. In this review, the relationship between vitamin D and cancer is discussed.